SOCIAL, ORGANIZATIONAL, DEMOGRAPHY AND INDIVIDUALS’ TECHNOLOGY ACCEPTANCE BEHAVIOUR: A CONCEPTUAL MODEL - Abbasi, Muhammad Sharif; Tarhini, Ali; Hassouna, Mohammed; Shah, Farwa (European Scientific Journal, ESJ, 2015)
The main aim of this paper is to propose a conceptual model of technology acceptance that explains how individual, social, organizational factors affect the users’ behavioural intention to use technology by academics for teaching and learning activities. More specifically, the proposed model extends the Technology Acceptance Model (TAM) to include nine constructs namely, peer influence, superior influence, resource facilitation, technology facilitations; self-efficacy, academic tasks, nonacademic tasks, government support, and finally, institute support. In addition, seven demographic and situational moderators (age, education level, organisation type, academic position, voluntariness and usage experience) are hypothesized to have a moderating effect on individuals’ acceptance behaviour. This model provides valuable insights into the factors that influence the acceptance or resistance of Internet and technology by intended users and offers opportunities for future research in understanding the acceptance of technology.